Analisa Pengaruh Kepimpinan Kepala Desa terhadap Pelayanan Publik di Desa Bongkot Berdasarkan Undang – Undang Nomor 25 Tahun 2009 - Yunus Rahmadani; H. Kuswanto; Muhammad Ajid Husain (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
Public service is an essential element in the implementation of village governance, aimed at providing direct benefits to the community. In this context, the leadership of the village head plays a strategic role in determining the direction of policies and the effectiveness of services provided to the community. This study aims to analyze the influence of the village head's leadership on the quality of public service in Bongkot Village, referring to Law No. 25 of 2009 on Public Service. The research method used is juridical-empirical with a qualitative approach, where data is collected through in-depth interviews, observations, and documentation related to policies and the implementation of public services in the village. The results show that the leadership of the village head in Bongkot Village is participatory and communicative. This leadership is reflected in openness to the aspirations of the community, the utilization of information technology, and the development of human resources to enhance the capacity of village officials. However, challenges remain, such as limited technological infrastructure that hinders more effective public service and the need for capacity building among village officials to carry out their duties more effectively. In conclusion, the leadership of the village head significantly influences the improvement of public service quality. Therefore, it is recommended that continuous training for village heads and their officials be conducted, along with policy support from local governments to create more responsive and efficient village governance.